Design and Classification of Implantable Antenna for Biomedical On Body and Off Body Communication - Soni, Gaurav Kumar; Yadav, Dinesh; Joshi, Ravi (International Journal of Electronics and Telecommunications, 2026)
In today's society, a significant global population depends on implantable medical devices as vital tools to maintain and improve their overall quality of life. Implantable antennas assume a crucial role in a myriad of applications, ranging from pacemakers and artificial organs to temperature monitors and blood-glucose sensors. Their substantial contribution significantly propels the progress of human well-being. In the field of biomedical applications, communication primarily relies on the use of Medical Implant Communication Services (MICS) and the Industrial, Scientific, Medical (ISM) band, ensuring seamless connectivity. This paper is dedicated to providing a thorough exploration of diverse design structures, classifications, and challenges associated with implantable antennas. Embedded within medical implants, these antennas function as integral components, enhancing human life in various applications. The discussion delves into intricate details regarding implantable antenna designs and classifications, shedding light on the nuanced challenges encountered by researchers and developers in this intricate domain. Ultimately, the overarching objective is to emphasize the transformative impact of implantable antennas on human life, fostering a comprehensive understanding of their versatile uses and applications in the field of biomedical.